KREATIVITAS MASYARAKAT MELALUI PEMBUATAN BAK SAMPAH DARI BAMBU SESUAI DENGAN KRITERIA USIA DI DESA PAMIJAHAN - viola jestia; Akbar Setiabella; Iwan Kurniawan; Lia Apriliani; Tita Hasanah (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2023)
The natural resources produced in Pamijahan Village are very abundant but the natural resources owned by Pamijahan Village have not been fully utilized by the community, even though there are a lot of natural resources in particular that can be used by the community to meet their needs, so there is a need for guidance or assistance to the community in increasing insight and skills in utilizing the potential of existing natural resources. Therefore, the purpose of this Community Service activity is carried out in an effort to help increase community creativity by utilizing the potential of natural resources, one of which is bamboo which is made into an innovative bamboo trash can. In general, the people of Pamijahan Village only make gates from bamboo and make saungs. It is possible to make innovations from bamboo, namely bamboo trash bins according to age criteria. The method used is through socialization and training in making innovations in trash bins made of bamboo. This activity involved PKK, GAPOKTAN (Farmers Group Association), Housewives, RW and RT throughout Pamijahan Village. The result of this socialization and training activity was that the participants seemed enthusiastic about the material presented, increasing their knowledge and insight about making bamboo trash bins according to age criteria